Principles of applying chemoexfoliation (chemical peelings) - Ewa Chlebus; Monika Serafin (Termedia Publishing House, 2023)
Chemoexfoliation (chemical peelings) is a costeffective and high safety profile method of affecting the skin to improve its appearance both for cosmetic conditions and to support the treatment of diseases associated with abnormal activity of sebaceous glands and hyperkeratosis. In this article, the authors provide a historical outline of the development of exfoliation techniques, the classification of peels on the basis of the depth of penetration, chemical functions of compounds, as well as practical tips on how to properly select the type of exfoliating substance depending on the disease or aesthetic problem of the skin. Also, possible complications, tips for their prevention and treatment are discussed.